The Reliability of the DEM Test in the Clinical Environment - Facchin, Alessio; Maffioletti, Silvio (Frontiers in Psychology, 2018)
The Developmental Eye Movement (DEM) test is a practical and simple method for assessing and quantifying ocular motor skills in children. Different studies have previously assessed the reliability of the DEM test and they have generally found high values for vertical and horizontal time, whereas those for Ratio and Errors were medium and low respectively. In the second application of test were found an improvement in performance in all subtests. Our aim was to evaluate the reliability of the DEM test using seconds and percentile scoring and looking in depth at the improvement in performance when the test is repeated. We tested the reliability of the DEM test on a group of 115 children from the 2nd to the 5th grade using different statistical methods: correlations, ANOVA, limits of agreement for results expressed in seconds and as percentile scoring and pass-fail diagnostic classification. We found high reliability with excellent values for vertical and adjusted horizontal time, medium-to-high for ratio and medium for errors. We have re-confirmed the presence of a significant improvement of performance on the second session for vertical time, horizontal time and ratio. The stability of binary classification of Pass-Fail criteria appears to be medium. We found high reliability for the DEM test when compared with the published results of other research but the improvement of performance, the learning effect was still present, but at a lower level than previously found. With the awareness of these limitations the DEM test can be used in clinical practice in evaluating performance over time.